The practice of effective inter-group communication among hospitality employees in a selected hotel. - Joned, Rusinah; Fong, Ching Shen; Omar, Zoharah (EuroJournals Publishing, Inc, 2008)
The study was to examine the relationship between level of knowledge, skills, and attitude with practice of effective inter-group communication. A total of 102 samples responded the questionnaires. The findings revealed that level of knowledge was high, whereas skill, attitude and practices were moderate. Correlation analysis showed that practices has a strong and significance relationship to skills, and attitude of effective intergroup communication, while, practices has a moderate and significance relationship to knowledge. Regression analysis showed that skills in effective inter-group communication were highly related to practices compare to other variables.